Molibden Nitrür Kaplamaların Aşınma Davranışı - Nilüfer, İ. Bülent (Fen Bilimleri Enstitüsü, 1998)
Geçiş metalleri nitrürlerinin ince-fılm kaplamaları önemli özelliklere ( yüksek sertlik, kimyasal kararlılık, taban malzemeye iyi yapışma, yabancı atomların yapınmasına karşı direnç) sahiptir. Bu tezin konusu olan molibden nitrürlerin bu gün için ticari üretimi söz konusu değildir, ancak aşınmaya dayanıklı sert kaplama olarak kullanım potansiyeli mevcuttur. Mo-N kaplamalar üzerine yapılmış araştırmalar sert kaplama özelliği, süper iletkenlik özelliği, yayınma özellikleri üzerinedir. Bu tez çalışmasında ark fiziksel buhar biriktirme yöntemi ile dört farklı azot kısmi basıncında (3,6,9, 11 mtorr) Mo-N kaplamalar üretilmiş ve bunların aşınma ve kesme performans deneyleri yapılmıştır. Aşınma deneyleri disk üzerinde kayan bilya yöntemiyle farklı yüklerde ( 5, 7, 10 N ) ve oda sıcaklığı, 200,400 ve 600 °C'ler de yapılmıştır. Oda sıcaklığında alumina bilya ile yapılan deneylerde 7 N yükte değişik azot basınçlarında kaplanan numunelerde sürtünme katsayısının 0.28-0.30 arasında değiştiği, 10 N yükte ise azot kısmi basıncının artmasıyla 0.45'ten 0.36'ya düştüğü belirlenmiştir. Molibden nitrür kaplamalarla karşılaştırılmak üzere aynı şartlarda değişik koşullarda TİN kaplanmış, numunelerin aşınma deneyleri yapılmış ve bu kaplamaların 10 N yükte alumina bilyaya karşı sürtünme katsayılarının molibden nitrür kaplamaların 1.5 ila 1.86 katı olduğu belirlenmiştir. Ayrıca TİN kaplamalarda yük artışına bağlı olarak sürtünme katsayısının artışı molibden nitrür kaplamalara göre çok daha yüksektir. 440 C paslanmaz çelik numunelerle yapılan deneylerde alumina bilya ile yapılan deneylere göre daha yüksek sürtünme katsayıları elde edilmiştir. 7N yükte yapılan deneylerde sürtünme katsayısı 0.71-0.74 arasında değişmiştir. 5N yükte yapılan deneylerde ise kaplama sırasındaki azot basıncının artmasıyla sürtünme katsayının 0.75'ten 0.64'e düştüğü görülmüştür. Yüksek sıcaklık deneylerinde deney sıcaklığının oda sıcaklığında 200 °C'ye yükseltilmesiyle sürtünme katsayısının arttığı, 400 ve 600°C'lere arttırıldığında ise oksidasyona bağlı olarak sürtünme katsayısının oda sıcaklığındaki değerinin bile çok altına düştüğü belirlenmiştir. Yüksek sıcaklık deneylerinden sonra numunelerin yüzeylerinde oluşan oksit fazlan X-ışını difraksyon yöntemiyle belirlenmiştir. Tüm molibden nitrür kaplı numunelerde 600°C deneyi sonrasında kaplamanın tamamen Mo(Ve dönüştüğü belirlenmiştir. Molibden Nitrür kaplamaların tornalama işleminde performanslarının belirlenmesi amacıyla torna plaketleri kaplanmış ve QG 26 malzemenin tornalanmasında denenmiştir. Bu performans deneyleri sonunda 6 ve 9 mtorr kısmi azot basıncında kaplanan molibden nitrür kaplamalı plaketlerin incelenen kesme hızlarında aşınma şerit genişliklerinin TİN kaplamaların şerit genişliklerinden daha düşük olduğu ve kesme hızının arttırılmasıyla Mo-N kaplamalardaki aşınma şerit genişliğinin artışının da TİN kaplamalara göre daha düşük olduğu görülmüştür.

Tribology can be defined as the study of the science and technology of the interacting surfaces in relative motion. This term can be divided into three subjects. These are "Friction", "Lubrication" and " Wear. Wear can be defined as the material loss due to material transfer from one to another surfaces which are in contact. Wear is typically effected by the material geometry, material hardness and environment condition. Wear can be separated into four general type; adhesive wear, abrasive wear, corrosion wear and surface fatique. Adhesive wear processes are initiated by the interracial adhesive junctions that form if solid materials are in contact on an atomic scale. As a normal load is applied, local pressure at the asperities becomes extremely high. In some cases, the yield stress is exceeded, and the asperities deform plastically until the real area of the contact has increased sufficiently to support the applied load. In the absence of surface films, the surface would adhere together, but very small amount of contaminant minimize or even prevent adhesion under normal loading. Abrasive wear occurs in contacts where one of the surfaces is considerably harder than the other or where hard particles are introduced into the contact. The harder surface asperities are pressed to the softer surface which results in plastic flow of the softer material around the hard one. When the harder surface moves tangentially, ploughing and removal of softer material takes place with grooves or scratches in the surface. Wear shortens the tool life in machining processes such as drilling, tapping, reaming, turning and milling. Wear of the tool materials results an extra cost in machining processes. Cutting tools faces wear because normal loads on the wear surfaces are high and cutting chips and the work piece which apply these loads are moving rapidly over the tools wear surfaces. The cutting action at related friction at these contact surfaces increase the temperature of the tool material which accelerates the physical and chemical processes associated with tool wear. Therefore, cutting tool wear is an economic penalty that must be accounted for in order to machine the part. Four main mechanisms of tool wear have been identified, namely adhesive wear, abrasive wear, delamination wear and wear due to chemical instability, including diffusion, solution and electrochemical wear, hi addition, there are some other wear modes on tools. They are flank wear, crater wear and build up edge. Flank wear is believed to be caused mainly by XVI abrasion of the tool by hard particles but there may be adhesive effects also. It is the dominating wear mode at low cutting speeds. Crater wear is the formation of a groove or a crater on the tool face, typically some 0.2-0.5 mm from the cutting edge, at the place where the chip moves over the tool surface. Ti is very commonly observed when cutting high melting point metals, like steel at relatively high cutting speeds. Crater wear is caused primarily by the dissolution of tool material by diffusion or solution wear since it occurs in the region of maximum temperature rise. Build-up edge of piled up work material near the tip of the cutting edge is frequently formed at intermediate cutting speeds. The build up edge is often unstable; it breaks away intermittently and is formed again. Depending on the materials and cutting conditions, influence of the build up edge may sometimes decrease or at other times increase the tool life. A stable built up edge can be beneficial and protect the tool surface from wear. On the other hand loose highly strain hardened fragments of the built-up edge may adhere to the chip or work piece and cause abrasion of the tool. At higher cutting speeds a built-up edge is less likely to form because the temperature increases and the build up edge is less likely to form because the temperature increases and the build-up edge can no longer support the stress of cutting and will thus be replaced by a flow zone. The wear of cutting tools takes place in three stages: In the initial wear stage, two materials have surface roughness irregularities in the form of protrusions or asperities. At the interface, asperities form the two materials touch defining contact areas. The total area from these contact is a fraction of asperities and partial removal may occur due to seizure accompanied by fracture of asperity or melting in asperity. As these asperities are removed, the initial surface roughness is altered and the contact area increases. If the force conditions mainly unchanged, the pressure decreases and the active wear mechanisms change to plasticity and/ or mild oxidation/ diffusion- dominated wear. This initial wear period will create small, visible wear surfaces. High technology today demands combination of diverse properties from a material which is generally unobtainable from a single or monolithic material. Coating technology has advanced rapidly in the past twenty years and it has greatly assisted in meeting such complex demands placed on materials. The important coating methods for high technology applications are plasma and detonation gun spraying techniques, electrodeposition, chemical vapor deposition and physical vapor deposition processes. During the last few years, great variety of hard coatings have been developed for improving the wear resistance of tools. For drilling tools, TEN is standard coating with high performance, but alternative coatings, e.g. Ti(C,N) and (Ti^l)N, are gaining increasing xvn importance. For special applications, new combination, ZrN and (Ti,Nb)N or MoN can provide additional advantages. Different physical vapor deposition processes such as reactive evaporation and cathodic arc plasma deposition process are especially suited to the reactive deposition of nitrides and carbides of a wide variety of pure metals and alloys. The term physical vapor deposition references a group of thin film deposition processes performed in vacuum and in which material is derived from a source by physical means, then deposited on a substrate. Thermal energy and ion bombardment are the methods used to convert the source material into a vapor. The primary deposition processes to be discussed are evaporation, sputtering and ion plating. Each one is in production use in areas where a given technique meets specific performance and commercial requirements. Evaporating, materials to be deposited are melted in either a resistively heated boat or by the heating action of a high-current electron beam. In either case, the material evaporates, and form a cloud of vapor which fills the deposition chamber. Condensation of this vapor on to the substrate produces the desired thin film. The atoms of the source materials in the vapor phase have very low energy, 0.2-2.6 eV and as a result, do not produce highly adherent or dense films when condensed onto the substrate. Despite this and other short comings of the process, evaporation probably continues to be the most widely used PVD technique. Molybdenum nitride which is the topic of this thesis has no commercial application today, but it is a potential material for wear resistant hard ceramic coating applications. The researches performed on molybdenum nitride are mostly for its super conducting and diffusion barrier properties. There are a few research on molybdenum nitride as a hard and wear resistant coating which obtained promising results. Molybdenum and nitrogen form four stable phases; a solid solution, p and y nitrides (MoiNx+O and 5 (MoN). P nitride is formed in tetregonal, y nitride is formed in cubic and 5 nitride is formed in hexagonal structure. Preparing 8 nitride phase is very hard. It is also very hard in plasma vapor deposition system, because it requires high ionization degrees and relatively high N2 partial pressure. Apart from these stable phases Mo-N system forms some metastable phases such as s and Bl-MoN. The aim of this investigation is to determine the effects of partial pressure on tribological properties of molybdenum nitride. In this thesis, molybdenum nitride coatings at four different nitrogen partial pressures are deposited on HSS steel substrates by cathodic arc plasma vapor deposition method and friction and wear tests are performed on these samples. In addition to friction and wear test performance of these coatings in cutting tools is tested. XVTLl To produce the coatings a arc plasma vapor deposition coating unit (Model NVT-12) was used. As nitrogen partial pressure 3, 6, 9, 11 mtorr values were selected. The aim in selecting higher nitrogen partial pressures than the ones used before in literature, is to be able to produce 5 nitride, MoN phase. After preparation of coatings, firstly XRD investigations were performed with Glancing Angle XRD. Cu Kalpha radiation was used. Results of this investigations show that the coating which were prepared at 3 and 6 mtorr nitrogen partial pressures consisted of cubic y M02N structure. The other samples prepared at 9 and 11 mtorr nitrogen partial pressures consisted of hexagonal 5-MoN structure. The thickness of the coatings produced varied between 1.5 to 2.3 um. The hardness of the molybdenum nitride coatings increases from 32000 to 39000 N/mm2 with the increase in nitrogen partial pressure in coating process. Ball on disk friction and wear tests are performed at different loads of 5,7,10 and at different test temperatures of 23, 200, 400, 600°C with alumina and 440 C stainless steel balls of 10 mm diameter. In the room temperature ball on disk tests performed with alumina ball, it is observed that friction coefficient varies between 0.28-0.30 at 7 N load depending on the nitrogen partial pressure in the ark plasma vapor deposition process. In the ball on disk tests performed with ION load, it is observed that with the increasing nitrogen partial pressure in plasma vapour deposition process, the friction coefficient decreased from 0.45 to 0.36. To compare with molybdenum nitride coatings, a series of titanium nitride coatings are deposited by the same method, on the same kind of samples at different bias voltage and nitrogen pressures. In ball on disk friction and wear tests performed with these samples, it is observed that friction coefficients of titanium nitride is 1.5 to 1.9 times of the ones observed from molybdenum nitride. In the ball on disk friction and wear experiments performed with 440 C stainless steel ball, higher friction coefficients are observed than alumina balls. At tests performed with 7N load, friction coefficient were between 0.71-0.74 and at tests with 5N load, friction coefficients decreased from 0.75 to 0.64 with the increasing nitrogen pressure applied in the plasma vapor deposition process. At high temperature tests, it is observed that by increasing the test temperature form room temperature to 200 °C, friction coefficient increased. Further increase in test temperature to 400°C and 600°C causes a decrease in friction coefficient. At 600°C experiments, friction coefficients are even less than the ones observed at room temperature. After high temperature XTX friction and wear tests, samples are cooled, the structures of coatings were analyzed by x-ray difraction method In all molybdenum nitride tested at high temperatures, it is observed that coating surfaces of all samples are completely covered with M0O3 layer. To determine the performance of molybdenum coatings on cutting tools for machining applications, molybdenum nitride and titanium nitride coatings are deposited on HSS triangle cutting tool samples containing 5 % cobalt. These tools are tested in machining of GG 26 grade gray iron cylinders in a ladthe and wear scar widths are measured. In performance tests, it is observed that the wear in molybdenum nitride coated tools deposited at 6 mtorr and 9 mtorr partial nitrogen pressure are less than titanium nitride tools at different cutting speeds in the range of 30 - 45 m /sn tested. It is also observed that increases in the cutting speed caused more wear in titanium nitride coated tools than molybdenum nitride coated tools. However, in dry cutting experiments at longer distances than 500 mm, the wear rate of molybdenum nitride coatings increased suddenly which resulted the higher wear rates than of titanium nitride coatings. This result is probably due to the increase in temperature of the samples which caused the change in the structure of molybdenum nitride coatings from nitrides to oxides when these tests were performed in dry cutting conditions.
trıbology Of Molybdenum Nıtrıde Coatıngs
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Aşınma davranışı; Kaplama; Molibden nitrür; Wear behavior; Coating; Molybdenum nitride